2021
DOI: 10.1097/gox.0000000000003784
|View full text |Cite
|
Sign up to set email alerts
|

Use of Absorbable Dermal Stapler in Reduction Mammoplasty: Assessing Technical, Quality-of-Life, and Aesthetics Outcomes

Abstract: Introduction: Reduction mammaplasty is a mainstay in the treatment of symptomatic macromastia, with a well-described positive impact on patient quality-of-life (QoL). Absorbable dermal staplers have the potential to improve the efficiency of skin closure in reduction mammoplasties, but a more comprehensive assessment of its impact on key outcomes has not been fully elucidated. Methods: A retrospective review of patients undergoing reduction mammoplasty between November 2018 and December 2020 was conducted. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…Our work demonstrates a significant reduction in operative time with the use of absorbable deep dermal staplers. This conclusion, involving both inferior and superior pedicle procedures, is largely aligned with other studies that have indicated faster closure times with dermal staples without sacrifice to aesthetic or functional outcomes 8–12,17 . Type of pedicle was not implicated as a significant predictor of changes in operative time, indicating that this trend is similar with both inferior and superior pedicles during reduction mammaplasty.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Our work demonstrates a significant reduction in operative time with the use of absorbable deep dermal staplers. This conclusion, involving both inferior and superior pedicle procedures, is largely aligned with other studies that have indicated faster closure times with dermal staples without sacrifice to aesthetic or functional outcomes 8–12,17 . Type of pedicle was not implicated as a significant predictor of changes in operative time, indicating that this trend is similar with both inferior and superior pedicles during reduction mammaplasty.…”
Section: Discussionsupporting
confidence: 76%
“…This conclusion, involving both inferior and superior pedicle procedures, is largely aligned with other studies that have indicated faster closure times with dermal staples without sacrifice to aesthetic or functional outcomes. [8][9][10][11][12]17 Type of pedicle was not implicated as a significant predictor of changes in operative time, indicating that this trend is similar with both inferior and superior pedicles during reduction mammaplasty. In context of increasing demand for reconstructive procedures, 18 reductions in operative time are favorable for optimizing workflow for surgeons and their teams.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This device is very familiar in our field, and the efficacy of this device is well established. 1 Within cosmetic surgery, the use of this device has been established in breast and facial rejuvenation, [2][3][4] and within reconstructive procedures, it has been proved effective for efficient closure of donor sites. 5 The application of this device extends to other surgical specialties mainly in obstetric, general, and orthopedic cases.…”
Section: Introductionmentioning
confidence: 99%